Temporal features of binocular rivalry - Noreika, Donatas; Švegžda, Algimantas; Stanikūnas, Rytis; Vanagas, Vygandas; Vaitkevičius, Henrikas (Psichologija, 2008)
Binocular rivalry is a phenomenon of visual perception in which perception alternates between two different images, presented to each eye’s resopective sites. Binocular rivalry has been investigated for decades, yet its nature has not been understood well. Most investigators agree now that rivalry is not a simple process but is based on complex interaction of hierarchical processes of visual system. Theoretical models are being created to describe binocular rivalry. One of the key things which the models have to explain is the temporal features of binocular rivalry: its dominant time distribution, the influence of the strength of the stimulus upon that etc. There is no agreement whether subtle temporal changes in presentation of stimuli are crucial for rivalry processes. The aim of the study was to investigate whether rivalry dominant time is influenced by flickering rate of stimuli presented to both eyes. 4 male subjects (mean age 31.8 y. with normal or corrected to normal vision) took part in the study. The stimuli were white round circles with a 45° slanting black line crossing it. The lines shown to different eyes were orthogonal to each other. Each line was subtended by 1.7 degrees. A special tachistoscope was constructed for presenting of the stimuli. In experiment 1 the stimuli were flickering in counter phase. The duration of the stimulus presentation was 5, 7, 10, 12, 15, 17, 20, 25, 30 ms. Moreover we also investigated dominant time under continuous stimuli presentation (constant view). In the second experiment the stimulus displayed to the right eye was flickering and the left one was kept steady. The subject had to press the corresponding key when he perceived the line displayed to the left eye. Dominant time was the time during which the corresponding key was pressed by the subject. Each subject took part in some 3 to 28 experiments. The results show that the flickering rate of the stimuli influences the dominant time. The function of mean dominant time versus the rate of the flickering is not a monotonic function – it has extremums with distance between two closest maximum or minimum being equal to about 5–12 ms. But the location of the extremums on the frequencies scale is not stable. We discuss a possible relation of the obtained results with the known neurophysiologic data and the theories of discrete perception.